Pelatihan Metode AHP untuk Penentuan Kriteria Pemilihan Vendor Perusahaan Berbasis Proyek Teknologi Informasi - Setiawan, Danang; Kusrini, Elisa; Jianul Hayat, Encep; Nugroho , Lulu Riesta (Journal of Appropriate Technology for Community Services, 2024)
In manufacturing companies, vendors supply raw materials for production. There are two vendor selection methods: the merit system and the lowest-cost method. Criteria and their weights are crucial in determining the winning vendor. One approach that can be taken is the AHP method, which is used for decision-making. This research contributes to vendor selection through AHP training and support. Determining vendor criteria is crucial for information technology project success, so AHP training is considered beneficial and has a positive impact on the company.